ISOMETRIC AND ISOMETRIC- m OPERATORS - Gunawan Gunawan (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This paper presents the definition, samples, and natures of isometric and isometric- m algebra operator for some in Hilbert space. In additions, the relationship of both operators will also be examined. To investigate natures of isometric and isometric- m operators, adjoint operators concepts and natures are required. Adjoint operator concept underlies isometric operator’s natures. Later, according to the concept, isometrc operator is expanded into isometric- m operators for some in Hilbert space. The result unveils algebra natures of isometric and isometric- m operators consisting of composition operators natures and multiplication with scalar. Furthermore, if T operators is isometric then T operators isometric- m for some .